Police officers, mental (ill-)health and spoiled identity - Bullock, Karen (Criminology & criminal justice, 2018)
This article considers the processes through which some police officers with mental ill-health experience stigmatization in police organizations. Situated in the sociological framework of Goffman and in modified labelling theory, it draws on the findings of a qualitative study and examines the sources of stigma embedded in police work, the consequences of stigma for the labelled officer, the nature of any resistance to the application of the label and approaches to challenging stigma within the policing context. It suggests that in order to tackle these negative attitudes constabularies must do more to address the processes of stigmatization associated with mental ill-health at the individual and institutional levels.